Towards parenthood : preparing for the changes and challenges of a new baby - Milgrom, Jeannette (ACER Press, 2009)
Towards Parenthood aims to assist soon-to-be and current parents manage the complex demands of parenting and strengthen the parent-infant relationship and the couple relationship. The book covers expectations of parenthood, skills in coping, problem-solving, enhancing self-esteem, assertive communication, bonding with your baby and understanding your baby's cues.
Keywords: Infants.; Infants -- Care.; Parenting.; Parent and infant.; Parents.; Psychology.; Social psychology.; Sociology.; Social sciences.; Parents; Popular Works; Education; Psychology; Publication Formats; Persons; Nuclear Family; Behavioral Sciences; Anthropology, Education, Sociology and Social Phenomena; Family; Named Groups; Publication Characteristics; Behavioral Disciplines and Activities; Psychology, Social; Sociology; Psychiatry and Psychology; Behavior and Behavior Mechanisms; Social Sciences; Infant Care; Parenting; Social Sciences.; Family & Marriage.; Sociology & Social History.; Nourrissons -- Soins.; Rôle parental.; Parents et nourrissons.; Psychologie.; Familles.; Sciences du comportement.; Psychologie sociale.; Sociologie.; Sciences sociales.; psychology.; behavioral sciences.; social psychology.; sociology.; social sciences.; parents.; FAMILY & RELATIONSHIPS -- Life Stages -- Infants & Toddlers.; Social sciences; Social psychology; Infants; Infants -- Care; Parent and infant